2010
DOI: 10.1016/j.asoc.2009.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The use of computational intelligence in intrusion detection systems: A review

Abstract: Intrusion detection based upon computational intelligence is currently attracting considerable interest from the research community. Characteristics of computational intelligence (CI) systems, such as adaptation, fault tolerance, high computational speed and error resilience in the face of noisy information fit the requirements of building a good intrusion detection model. Here we want to provide an overview of the research progress in applying CI methods to the problem of intrusion detection. The scope of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
248
0
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 561 publications
(278 citation statements)
references
References 189 publications
0
248
0
10
Order By: Relevance
“…Tsai et al (2009) reported there have been 30 major IDS studies used KDDCup 1999 datasets in their research. According to Wu and Banzhaf (2010), KDDCup 1999 dataset is the largest publicly available and sophisticated benchmarks for researchers to evaluate intrusion detection algorithms or machine learning algorithms. Figure 2 shows data used in the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsai et al (2009) reported there have been 30 major IDS studies used KDDCup 1999 datasets in their research. According to Wu and Banzhaf (2010), KDDCup 1999 dataset is the largest publicly available and sophisticated benchmarks for researchers to evaluate intrusion detection algorithms or machine learning algorithms. Figure 2 shows data used in the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…This model was then utilized to predict network behavior during detection stage (Yang et al, 2005). However, it is important to note that intrusions usually polymorph and continuously evolve (Wu and Banzhaf, 2010). Therefore, it resulted in poor performance.…”
Section: Adaptive Intrusion Detection Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensors may thus feed the system with bad (bogus) information, or fail to report something that has actually happened. We distinguish both cases from the usual false positives and false negatives [8], as they clearly have an intentional nature. These two cases are widely explained in Section 2.2.…”
Section: Monitoring Systemmentioning
confidence: 99%
“…In this sense, many research works in IDS-based solutions make use of the concept of time window, where events are gathered in a given period of time of, for example, two seconds [8].…”
Section: Behavioural Sensor Modellingmentioning
confidence: 99%